FACTORS INFLUENCING THE DEVELOPMENT OF CONSCIOUS READING IN PRIMARY SCHOOL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article investigates the multifaceted factors influencing the development of conscious reading skills among primary school students. Conscious reading is conceptualized as an integrative literacy competence encompassing decoding accuracy, comprehension, critical reflection, and metacognitive regulation. Drawing on international research trends and the Early Grade Reading Assessment (EGRA) framework, the study examines pedagogical, cognitive, socio-cultural, and institutional factors shaping early reading development. A mixed-methods research design was employed, involving EGRA-based diagnostic assessments, classroom observations, teacher questionnaires, and semi-structured interviews. The findings demonstrate that systematic instruction, teacher professional competence, formative assessment, and family literacy environments significantly affect students’ conscious reading outcomes. The study offers evidence-based recommendations for improving primary reading instruction and aligning national practices with global literacy standards.